2016
DOI: 10.1016/j.ijcard.2015.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of conversion from mycophenolate mofetil to everolimus for the development of cardiac allograft vasculopathy in maintenance of heart transplant recipients

Abstract: Conversion to EVL from MMF in maintenance periods after HTx may decrease the rate of CAV progression based on IVUS indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
(79 reference statements)
1
21
1
1
Order By: Relevance
“…17,19,30 Our present results show that DA was independently associated with worsening of morphological change on IVUS in the first post-HTx year regardless of EVL initiation during this year. Because our recipients seldom received EVL during the first post-HTx year (14.3% of all subjects and 20.8% in the DA group), this observation may be of limited significance.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…17,19,30 Our present results show that DA was independently associated with worsening of morphological change on IVUS in the first post-HTx year regardless of EVL initiation during this year. Because our recipients seldom received EVL during the first post-HTx year (14.3% of all subjects and 20.8% in the DA group), this observation may be of limited significance.…”
Section: Discussionsupporting
confidence: 49%
“…30 Our previous study revealed that conversion to EVL from MMF in the maintenance of heart transplant recipients reduced worsening of morphological changes on IVUS compared with continuing MMF. 19 In our present study, the DA group tended to be converted to EVL from MMF during 3 years post-HTx compared with the DA-free group; nevertheless, the DA group experienced an ongoing reduction in luminal volume after 1 year post-HTx. On the other hand, the observational design of our study might prevent exact understanding of the correlation between EVL initiation and CAV progression after 1 year post-HTx.…”
Section: Discussioncontrasting
confidence: 44%
“…Nine of these studies had a randomized controlled design, thus supporting strong evidence of the findings [73][74][75][76][77][78][79][80][81]. Most of studies (58%) investigated the effect of mTOR inhibitors (sirolimus or everolimus) in comparison with calcineurin inhibitors (CNIs, cyclosporin or tacrolimus) or to mycophenolate derivatives (MMF) [74,[76][77][78][79][80][82][83][84][85][86]. The other agents investigated for CAV prevention included induction therapies, tacrolimus versus cyclosporine, Ace inhibitors, aspirin, statins and granulocyte-colony-stimulating factor [73,75,81, [87][88][89][90][91][92][93].…”
Section: Prevention Of Cavmentioning
confidence: 99%
“…The low long-term tolerability of sirolimus may partially explain these findings, because more patients were discontinued sirolimus, than MMF, possibly contributing to the balancing of the outcomes. In addition, two studies, one of which randomized [78,83], found that late conversion to everolimus or sirolimus seems ineffective, possibly related to the difference in plaque composition at various stages of CAV development, while another small retrospective study supports opposite results with everolimus delaying late CAV progression [86]. Overall, these findings are in line with the reports discussed above about pathology and the CAV risk factors, supporting the model of two stages and morphologies CAV development: a first phase more related to immuno-inflammatory injury, characterized by concentric intimal hyperplasia, and a later phase in which the contribution of metabolic risk factors becomes more relevant, resulting in a different plaque and morphology composition, resembling that of native atherosclerosis.…”
Section: Immunosuppressive Treatmentsmentioning
confidence: 99%
“…Autorzy sugerują, że korzystne efekty mogły stanowić wynik połączenia EVE z takrolimusem. Większość pacjentów we wcześniej opisanych badaniach przyjmowała EVE z cyklosporyną [28].…”
Section: Leczenieunclassified